The Influence of the Discovery Learning Model on the Ability to Find Intrinsic Elements in Short Stories - Kristiana, Heni; Wesa Atmaja, I Wayan; Triwahyuni, Eges (Journal of Education Technology and Inovation, 2023)
Text for abstract. Type your abstract Font Calibri here (10pt). An abstract (minimum 150 word, maximum 200 words) is typed single space. The abstract should be written briefly and factually in English, and be written separately from the article. The abstract contains a clear elaboration of (1) background or research purpose, (2) methods, (3) results, and (4) conclusion. Short stories are one of the literary works that are interesting to read. Most of the stories in short stories are purely fictional; however, the stories in short stories have relevance to real life because the sources of the stories that occur in short stories partly come from human life. The aim of this research is to determine the effect of the discovery learning model on students' ability to determine the intrinsic elements of short stories. The method used in this research is quantitative in the form of an experiment with a one-group pretest-posttest design. Data analysis in hypothesis testing uses a paired sampling t-test. The results of the research show that the value of the paired sample t-test shows that the sign value is 0.000 with a result of less than 0.05, which means that there is an influence of discovery learning on students' ability to determine the intrinsic elements of short stories in class XI of SMK Negeri 1 Jember